PERNIKAHAN DALAM AL-QUR’AN: Telaah Kritis Pernikahan Endogami dan Poligami - Muhim Nailul Ulya (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2021)
Endogamous marriage and polygamous marriage. These two types of marriages have several problems of their own, both in terms of rules and social ethics. Thus the aim of the researcher is to find out about marriage in the Qur'an (a critical study of endogamous and polygamous marriages). This study uses a maudhu'i interpretation approach, a method of interpretation that seeks to find answers to the Koran by collecting verses of the Koran that have one purpose, which together discuss certain topics/titles and put them in order according to the period of their descent is in accordance with the causes of their descent, then pay attention to these verses with explanations, explanations and their relationships with other verses, then consider the laws. The research question to be answered is marriage in the Qur'an (a critical study of endogamous and polygamous marriages). Based on the results of the research that the author has done, it is concluded that marriage, with all the rules set out in it, has a noble goal, namely to obtain peace and happiness in life. A marriage that does not produce peace in his days, then the marriage has the potential to fail. In achieving this goal, humans with all religious norms and social norms that apply in their environment, have their own terms and conditions in determining a married couple. This is not prohibited as long as everything is intended for the common good and neither party has any objections and is treated unfairly. Because marriage is a sacred worship that involves both people in order to achieve peace of mind which is a shared goal.